Causes of Collapsed On-Site Wastewater Management Systems within Benin City, Edo State, Nigeria - J. E. Osunbor; G. E. Evbaru-Okhuaihesuyi; J. O. Ehiorobo (Journal of Applied Sciences and Environmental Management)
On-site wastewater management systems play a pivotal role in domestic wastewater management. However, their structural failure poses significant risks to human lives and can result in environmental hazards. Hence the objective of this paper was to investigate the causes of collapsed on-site wastewater management systems within Benin City, Edo State, Nigeria using appropriate standard techniques after collecting soil samples from 3 collapsed on-site wastewater management systems within the area of study. Data obtained reveals that the soil types investigated alternated between A-2-4 and A-2-6 Silty and Clayey soils according to AASHTO classification. Specific gravity test result values ranged from 2.54 to 2.62, and the gradation test from 9.87 to 17.25 for the 0.75micron sieve. The liquid limit ranges from (21.34 to 30.99) % and the plasticity index ranges from (0 to 17.44) %. Compaction results show that the soil has its maximum dry density (MDD) ranging from (1.79 to 1.90) g/cm3 and its optimum moisture content from (8.8 to 14.0) %. While the triaxial test has its cohesion ranging from (2 to 26) % and its angle of internal friction as (8.03 to 20.54) oC. Reasons deduced to have been the cause of the observed variations in the strength properties and cohesion values of the soil samples of the same location include differences in soil composition, stress history, sample collection technique, and laboratory testing variability.